THE IMPACT OF CSR ON ROMANIAN CONSUMERS’ TRUST - MAICAN, Silvia (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
the present article presents a small part of a doctoral research meant to determine the way the Romanian consumers perceive companies’ socially responsible activities. The aim of the present article is to emphasize the impact that companies’ socially responsible activities have on consumer trust. There were 650 questionnaires applied during September 2014 and January 2015 with the help of GoogleDocs. The collected data were analysed using SPSS software.  The results show that consumers give more trust to companies that are socially responsible than to the ones that are not. In the end, this trust brings loyalty and profits to those companies, in this way, both the company and society wins.